The Influence of Digital Competencies and AI Integration on Islamic Teachers’ Functional Skills in Southern Pakistan - Muhammad Kashif Majeed; Sumera Irfan; Desfa Yusmaliana; Tunku Badariah Ahmad; Aizat Bin Shamsuddin (Universitas Muhammadiyah Bangka Belitung, 2026)
This study investigates digital competencies and their interfacing with AI in the Islamic secondary schools of Southern Pakistan and its impact on teachers’ functional skills. Integration of artificial intelligence and digital skills into the education process can set an important agenda on questions related to teacher performance, technology skill development. This quantitative study analyzes 450 responses from a sample of 450 Islamic school teachers by using SPSS 22. according to study criteria. The impact of digital competencies and AI usage on functional teaching skills was evaluated by means of a multiple linear regression method. The results reveal that the use of AI tools did not make any difference in terms of communication skills as the values of their significance (0.073 > 0.05) exceeded the threshold. Nevertheless, digital competences had significant influence on all functional skills, but with a significance value of 0.000 < 0.05. The findings indicate the importance of the digital skills in contemporary education and points to the gap for AI application among rural Islamic school teachers. The contribution to this study was to help with teacher digital readiness, AI adaptation and professional skills enhancement. The insights offer recommendations for improving educational practices, technology integration policy, and teacher development programs in Southern Pakistan that will be valuable for implementing in its context.